The potential protective role of Parkinson’s disease against hypothyroidism: co-localisation and bidirectional Mendelian randomization study - Lei, Jiang; He, Wenxuan; Liu, Yao; Zhang, Qinxin; Liu, Yingyao; Ou, Qican; Wu, Xianli; Li, Fenglin; Liao, Jiajia; Xiao, Yousheng (Frontiers in Aging Neuroscience, 2024)
Background The association between hypothyroidism and Parkinson’s disease (PD) has sparked intense debate in the medical community due to conflicting study results. A better understanding of this association is crucial because of its potential implications for both pathogenesis and treatment strategies. Methods To elucidate this complex relationship, we used Bayesian co-localisation (COLOC) and bidirectional Mendelian randomization (MR) analysis. COLOC was first used to determine whether hypothyroidism and PD share a common genetic basis. Subsequently, genetic variants served as instrumental variables in a bidirectional MR to explore causal interactions between these conditions. Results COLOC analysis revealed no shared genetic variants between hypothyroidism and PD, with a posteriori probability of hypothesis 4 (PPH4) = 0.025. Furthermore, MR analysis indicated that hypothyroidism does not have a substantial causal effect on PD (OR = 0.990, 95% CI = 0.925, 1.060, p = 0.774). Conversely, PD appears to have a negative causal effect on hypothyroidism (OR = 0.776, 95% CI = 0.649, 0.928, p = 0.005). Conclusion Our findings suggest the absence of shared genetic variants between hypothyroidism and PD. Interestingly, PD may inversely influence the risk of developing hypothyroidism, a finding that may inform future research and clinical approaches.